Eficacia de la clorhexidina sobre microorganismos de la cavidad bucal. Revisión bibliográfica - Arciniega Aguilar, Stefania Carolina (2021)
Chlorhexidine is an oral antiseptic considered "gold standard", due to it is a broad spectrum, bacteriostatic, bactericidal agent with a high substantivity of 8 to 12h; used as a coadjuvant during mechanical oral hygiene. This research aimed to analyze the efficacy of chlorhexidine recognizing the microorganism (s) with the highest sensitivity to chlorhexidine, compare its efficacy against other antiseptics and identify its most optimal concentration on oral microorganisms, conducting a descriptive and comparative bibliographic review by searching for articles or thesis indexed in databases such as PubMed, Scielo and Google Scholar; taking as reference 30 scientific articles. In this review, it was found that the most susceptible microorganisms to CHX (Chlorhexidine) were Streptococcus mutans followed by Porphyromonas gingivalis, Lactobacillus acidophilus, and Streptococcus salivarius, due to that these presented greater halos of inhibition than the other microorganisms. CHX was highly effective compared to commercial mouthwashes (essential oils, cetylpyridinium chloride, fluorine and xylitol,); as on mouthwashes based on natural compounds, since with a lower minimum inhibitory concentration CHX achieved a greater zone of inhibition against microorganisms. In addition, it was found that at a concentration of 0,2% was more effective but with a greater possibility of adverse effects. Concluding that chlorhexidine is a very effective antiseptic by inhibiting the growth of microorganisms at the oral level. Key Words: Chlorhexidine, mouthwash, oral antiseptic, bactericide.